2018
DOI: 10.1055/s-0038-1675801
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mannose-Binding Lectin Gene Polymorphisms and the Serum MBL Level for the Early Detection of Neonatal Sepsis

Abstract: Background Mannose-binding lectin (MBL) is a component of innate immunity and is particularly important in neonates, in whom adaptive immunity has not yet completely developed. MBL deficiency and MBL2 gene polymorphisms are associated with an opsonization defect and have been associated with neonatal sepsis. Aim The aim of our study was to assess serum MBL levels and genotype MBL2 genes to determine whether they can serve as markers for predicting neonatal sepsis in neonatal intensive care units. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…The genotype frequencies of the SNPs in our study were in agreement with previous published data among the Egyptian population; the genotype frequency of rs1800451 was similar to the frequency found by Badawy and colleagues in Egyptian population [ 23 ], as well as those from studies in other populations [ 14 , 37 ]. The genotype frequency results of rs1800450 were very similar to that found by Nasr et al in a recent study in an Egyptian population, with frequencies of 41.7%, 58.3%, 0.0% for the AA, AB and BB genotypes, respectively [ 38 ], similar to the results found by Badawy and colleagues [ 23 ]. The notable high frequency associated with these variants was observed previously, and attracted much attention, leading to many different hypotheses and an resolved debate concerning the real roles of these variants [ 18 , 19 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The genotype frequencies of the SNPs in our study were in agreement with previous published data among the Egyptian population; the genotype frequency of rs1800451 was similar to the frequency found by Badawy and colleagues in Egyptian population [ 23 ], as well as those from studies in other populations [ 14 , 37 ]. The genotype frequency results of rs1800450 were very similar to that found by Nasr et al in a recent study in an Egyptian population, with frequencies of 41.7%, 58.3%, 0.0% for the AA, AB and BB genotypes, respectively [ 38 ], similar to the results found by Badawy and colleagues [ 23 ]. The notable high frequency associated with these variants was observed previously, and attracted much attention, leading to many different hypotheses and an resolved debate concerning the real roles of these variants [ 18 , 19 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a prospective Dutch study found no association between MBL2 genotypes and the susceptibility to CAP and that MBL2 genotypes could not be considered as factors with major risk for developing infection with CAP [ 49 ]. In addition, regarding neonatal sepsis in an Egyptian population, although an Egyptian cross sectional study found a prevalence of mutant allele B with neonatal sepsis that might indicate a possible role of allele B of codon 54 in neonatal sepsis [ 50 ], another case-controlled study with a larger sample size was conducted on neonates in an Egyptian population and found no association of MBL2 SNPs with sepsis risk [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Our study revealed that the B allele was expressed in significantly higher percentages of RAS patients (42.5%) than controls (16.3%). In contrast, no significant association could be detected between the MBL2 codon 54 genotypes and severe chronic periodontitis 41 , neonatal sepsis, 42 and recurrent respiratory tract infection in children. 43 Among the 40 RAS patients in our study, 29 (72.5%) had minor ulcers, 8 (20.0%) patients had major ulcers, and 3 (7.5%) patients had herpetiform ulcers.…”
Section: Resultsmentioning
confidence: 72%
“…Cumulative evidence confirmed that a low serum MBL concentration resulting from O was associated with a higher incidence of sepsis in all age groups (20,26,(42)(43)(44)(45)(46). Unfortunately, this theory did not hold in observations focused on neonatal sepsis, in which no such correlation was found (18,21,24,25,(47)(48)(49). The mixed data mentioned above raise the question as to the exact role of MBL2 in neonatal sepsis.…”
Section: Mannose-binding Lectin (Mbl)mentioning
confidence: 99%